Pathogenic Acinetobacter species including the novel Acinetobacter dijkshoorniae recovered from market meat in Peru - Marí-Almirall, Marta; Cosgaya, Clara; Pons, Maria J; Nemec, Alexandr; Ochoa, Theresa J; Ruiz, Joaquim; Roca, Ignasi; Vila, Jordi (International journal of food microbiology, 2019)
Species of the Acinetobacter calcoaceticus-Acinetobacter baumannii complex are important human pathogens which can be recovered from animals and food, potential sources for their dissemination. The aim of the present study was to characterise the Acinetobacter isolates recovered from market meat samples in Peru. From July through August 2012, 138 meat samples from six traditional markets in Lima were cultured in Lysogeny and Selenite broths followed by screening of Gram-negative bacteria in selective media. Bacterial isolates were identified by MALDI-TOF MS and DNA-based methods and assessed for their clonal relatedness and antimicrobial susceptibility. Twelve Acinetobacter isolates were recovered from calf samples. All but one strain were identified as members of the clinically-relevant Acinetobacter calcoaceticus-Acinetobacter baumannii complex: 9 strains as Acinetobacter pittii, 1 strain as A. baumannii, and 1 strain as the recently described novel species A. dijkshoorniae. The remaining strain could not be identified at the species level unambiguously but all studies suggested close relatedness to A. bereziniae. All isolates were well susceptible to antibiotics. Based on macrorestriction analysis, six isolates were further selected and some of them were associated with novel MLST profiles. The presence of pathogenic Acinetobacter species in human consumption meat might pose a risk to public health as potential reservoirs for their further spread into the human population. Nevertheless, the Acinetobacter isolates from meat found in this study were not multidrug resistant and their prevalence was low. To our knowledge, this is also the first time that the A. dijkshoorniae species is reported in Peru.
Keywords: Acinetobacter; Taxonomy; zvířata; antibakteriální látky; Peru; multilokusová sekvenční typizace; infekce bakteriemi rodu Acinetobacter; Antimicrobial resistance; Microbial Sensitivity Tests; Cattle; mikrobiální testy citlivosti; Animals; Meat; maso; Food Contamination; Epidemiology; Cattle Diseases; kontaminace potravin; nemoci skotu; skot; Multilocus Sequence Typing; lidé; Humans; Acinetobacter Infections; Food-producing animals; Anti-Bacterial Agents